2019
DOI: 10.12659/msm.916907
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to Lymphocyte Ratio and Glucocorticoid Resistance in Newly Diagnosed Primary Immune Thrombocytopenia: A Retrospective Cohort Study

Abstract: Background: In China, evidence regarding to the association between platelet to lymphocyte ratio (PLR) and glucocorticoid (GC) resistance in participants with primary newly identified immune thrombocytopenia (ITP) is limited. We aimed to investigate whether PLR is independently linked with GC-resistant ITP. Material/Methods: We non-selectively and consecutively collected 154 newly diagnosed ITPs. The start enrollment time and the end enrollment time were from March 2013 to June 2017. The independent and depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In our study, pregnant patients with ITP who failed first-line therapy with higher baseline PLR levels were more responsive to rhTPO. This result is consistent with that of a previous study [14]. In addition to its direct role in stimulating platelet production by megakaryocytes, rhTPO has demonstrated additional effects on immune regulation [10,11].…”
Section: Table 4 Outcomes In Rhtpo Groupsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, pregnant patients with ITP who failed first-line therapy with higher baseline PLR levels were more responsive to rhTPO. This result is consistent with that of a previous study [14]. In addition to its direct role in stimulating platelet production by megakaryocytes, rhTPO has demonstrated additional effects on immune regulation [10,11].…”
Section: Table 4 Outcomes In Rhtpo Groupsupporting
confidence: 93%
“…Moreover, the clinical predictors associated with the therapeutic effects of rhTPO remain unclear. Studies have demonstrated a correlation of mean platelet volume (MPV) [12,13] and platelet-to-lymphocyte ratio (PLR) [14,15] with the efficacy of treatment in ITP patients. However, to our knowledge, no studies have investigated the relationship between these predictors and the therapeutic efficacy of rhTPO in pregnant patients with ITP.…”
Section: Introductionmentioning
confidence: 99%